Model study of screw pile installation impact on ground disturbance and vertical bearing behaviour in dense sand. Issue 1 (April 2021) - Saleem, Muhammad Azhar; Malik, Adnan Anwar; Kuwano, Jiro
Abstract: The purpose of present study was to understand the behaviour of model scale closeended single helix pile using dense ground conditions with a special focus on installation impact it creates on the nearby ground disturbance and its associated vertical bearing characteristics. To understand ground disturbance behaviour, model scale pile load testing was conducted both with and without installation mechanism. Screw piles having large helix to shaft diameter were also incorporated in the study to investigate helical size impact on nearby ground disturbance; and therefore, variation in their bearing behaviour. Variation in installation effort (installation load and torque) for piles having large helix to shaft diameter was also investigated. Based on experimental results, it was observed that the installation of screw piles disturbed the ground significantly along the pile shaft whereas ground disturbance below the pile tip was almost negligible. In addition, with the increase in helix to shaft diameter, ground disturbance ratio was increased. With the increase in helix to shaft diameter, installation effort requirements increased significantly. Moreover, with the increase in helical diameter, end bearing of the pile was increased but there was no effect on skin friction owing to the same shaft diameter.